Mobility Based Secure Localization in Underwater Wireless Sensor Networks - Shanthi M B, Ms; Dinesh K Anvekar, Dr (International Journal of Engineering and Technology, 2018)
Currently, many applications require environmental sensing inside water bodies; Underwater Wireless Sensor Network (UWSN) is a new breed of sensor networks which achieve this sensing task. However, UWSN faces unique challenges due to signal problems associated with water medium. Most of the UWSN nodes have limited resources, and require Node Localization technique to identify their location. Many effective node localization techniques have been proposed in the literature. However, a new challenge has emerged related to security of the node localization technique; intruder or compromised sensor nodes provide incorrect localization information to the localization process, which may result in network disconnection. Currently, effective solution to address this problem in the literature is still lacking. In this work, a secure localization technique based on node mobility and probabilistic model is presented. This proposed localization technique, substantially outperforms the contemporary technique in-terms of security effectiveness when demonstrated empirically..